Design of Maize (Zea Mays) Planters and Fertilizer Dibble Stick-Type Semi-Mechanical Ergonomics - Sugiana, I Wayan; Gunadnya, Ida Bagus Putu; Setiyo, Yohanes (Jurnal BETA (Biosistem dan Teknik Pertanian), 2017)
The purpose of this research was to get a prototype of a maize planters and fertilizer that can simplify work of farmers in the cultivation of maize, especially planting and fertilizing in one work process. The method used in this research is to create a prototype of a planter and corn fertilizer semi-mechanical that tested on 100 m2 of land no-tillage with flooded conditions 2-3 days before planting at a spacing of 25 cm in a row and 75 cm between rows. The results of the test show that the average output of corn was 2 seed to each hole and 31-40 grams fertilizer with a success rate of 86,88 % and 95 %, effective field capacity 0,0122 ha/hour, theoretical field capacity 0,0135 ha/hour and the speed of planting was 12 hole/minute.